New General Theory of Magnitudes - Weinstock, Daniel (Eximia, 2024)
This paper shows a new way to get the distance between any 2 stars shown on a photograph of the night sky of the stars anywhere at all . Each star is shown as Inverse Apparent Magnitudes.